Law Enforcement Of Spreading False And Misleading News In Pandemic Covid-19 Era - Hartanto, Hartanto; Astuti, Dwi; Syakdiah, Syakdiah (JURNAL LEGALITAS, 2025)
The Covid-19 pandemic that has hit the world since early 2020 has had an impact on various aspects including the fields of communication and information. Several cases had ended  in the legal realm relate to the ITE Law. This research examines cases of fake and misleading news that are widespread in Indonesia, in 3 fields, namely Health, Government and General Elections. The urgency of fake news  related to consumer losses. Not all fake news causing consumer harm. What are the factors that delays in law enforcement for criminal acts of spreading false and misleading news related to the pandemic and what efforts should be made to deal with it? This research uses normative juridical methods with secondary legal materials; Criminal acts conected to spreading fake news are regulated in the qualifications of Article 35 of the ITE Law 11/2008, which places more emphasis on the phrase manipulation and destruction of information if the result arises, namely consumer losses, then Article 28 (1) of the ITE Law is imposed. Meanwhile, those that cause riots in society in general can be recognized as Article 28 (3).